Community based descriptive study on assessment of nutritional status among preschool children Pullipakkam village, Tamil Nadu - H., Gladius Jennifer; P. A., Archana Lakshmi (International Journal Of Community Medicine And Public Health, 2018)
Background: Nutrition assessment is to obtain precise information on the prevalence of nutritional problems and identification of individuals at risk. 25.7% of Indian children under five years were underweight and 28.6% were stunted due to chronic under nutrition, India accounts for more than 3 out of 10 stunted children in the world. Under nutrition is substantially higher in rural areas. Hence, this study conducted. The objective of the study was to assess the nutritional status of preschool children (1-5 years) in Pullipakkam, field practice area of KIMSRC. Methods: An observational study conducted in Pullipakkam from January 2017 to February 2017. 75 children aged 1–5 years were selected by simple random sampling. After getting informed consent from parents, Data were collected using structured questionnaire by interview method. Chi square test at 5% α were calculated by using SPSS 20V. Results: Among 75 children, stunting (52.8%), wasting (62.3%), mid arm circumference less for age (13.3%). 73% had inadequate calories intake. There was no significant association (p>0.05). Conclusions: The nutritional status of the children usually remains under question. Parents have to be properly health educated on balanced diet with locally available low cost foods has to given.